2006
DOI: 10.1021/ac0610558
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrochemical Properties of Carbon Films Prepared by a Electron Cyclotron Resonance Sputtering Method

Abstract: This paper describes the characterization, electrochemical properties, and applications of carbon films prepared by the electron cyclotron resonance (ECR) sputtering method. The ECR-sputtered carbon film was deposited within several minutes at room temperature. The optimized sputtering conditions significantly change the film structure, which includes many more sp3 bonds (sp3/sp2 = 0.702) than previously reported film (sp3/sp2 = 0.274)1 with an extremely flat surface (0.7 A). The ECR-sputtered carbon films exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 63 publications
6
89
0
Order By: Relevance
“…9,16 We also reported that electrochemical properties of pure-UBM nanocarbon film electrodes changed by changing the ion acceleration voltage. When we increased the acceleration voltage during sputtering, the potential window became wider with increasing sp 3 bond content.…”
Section: Potential Window and Basic Electrochemical Propertiesmentioning
confidence: 90%
“…9,16 We also reported that electrochemical properties of pure-UBM nanocarbon film electrodes changed by changing the ion acceleration voltage. When we increased the acceleration voltage during sputtering, the potential window became wider with increasing sp 3 bond content.…”
Section: Potential Window and Basic Electrochemical Propertiesmentioning
confidence: 90%
“…For the potential application of a certain kind of carbon material in electrochemistry, the basic electrochemical behaviors should be first studied to determine several important parameters of carbon electrodes [47,73,74]: electrochemical potential window, electron transfer rate, redox potentials, etc.…”
Section: Basic Electrochemistry Of Graphenementioning
confidence: 99%
“…31 Briefly, we cut the carbon material into rectangles, and then fixed a plastic tape with a 2 mm diameter hole in it onto these carbon films to form disk electrodes. They were used as base film electrodes, since they have been proved to provide good electron transfer that can successfully detect many redox species or biomolecules.…”
Section: Preparation Of a Uv/ozone Treated Cnf Modified Electrodementioning
confidence: 99%